Fault lines - Pryce-Jones, David 1936- (Criterion Books, 2015)
"Born in Vienna in 1936, David Pryce-Jones is the son of the well-known writer and editor of the Times Literary Supplement Alan Pryce-Jones and Therese "Poppy" Fould-Springer. He grew up in a cosmopolitan mix of industrialists, bankers, soldiers, and playboys on both sides of a family, embodying the fault lines of the title: "not quite Jewish and not quite Christian, not quite Austrian and not quite French or English, not quite heterosexual and not quite homosexual, socially conventional but not quite secure." Graduating from Magdalen College, Oxford, David Pryce-Jones served as Literary Editor of the Financial Times and the Spectator, a war correspondent for the Daily Telegraph, and Senior Editor of National Review. Fault Lines ... a memoir that spans Europe, America, and the Middle East and encompasses figures ranging from Somerset Maugham to Svetlana Stalin to Elie de Rothschild ... has the storytelling power of Pryce-Jones's numerous novels and non-fiction books, and is perceptive and poignant testimony to the fortunes and misfortunes of the present age"...